A Low‐Power Miniaturized 315 MHz Transceiver Module for Biosignal Transmission. Issue 12 (17th November 2014) - Maenaka, Kazusuke; Chan, Alex Chun Kit; Ohkochi, Sayaka; Nakamura, Toshiaki; Kitamura, Hirokazu; Kimura, Junichi; Higuchi, Kohei
SUMMARY In this paper we describe a small‐sized and extremely low–power consumption transceiver module for a wireless sensor network, especially suitable for biosignal transmission. Currently, many types of transceiver modules such as Bluetooth, ZigBee, and low‐power radio modules for 315 MHz are available on the market. However, when we consider an extremely small and light system including a battery and transceiver module for a wireless sensor network mounted on the human body, almost all the transceiver modules on the market consume too much power and are too large for assembly. In this study we concentrated on creating an extremely low–power consumption and small/lightweight transceiver module for the 315 MHz radio band. As a result, we successfully designed and fabricated a transceiver module with a size of 11 × 11 × 1.5 mm3 including a bipolar ASIC for the radio circuit and an eight‐bit microcontroller. The operation currents of the receiver and transmitter are 2 mA and 1 mA, respectively, for a supply voltage of 2.5 V. These results are generally sufficient for many uses for wireless sensor network systems, and not only for biosignal applications.